2012
DOI: 10.1177/1947601912458585
|View full text |Cite
|
Sign up to set email alerts
|

Cas and NEDD9 Contribute to Tumor Progression through Dynamic Regulation of the Cytoskeleton

Abstract: The Cas family proteins, p130Cas (Cas) and NEDD9, are adaptor molecules that regulate cytoskeletal dynamics to promote multiple cellular processes, including migration, invasion, proliferation, and survival. Because these functions are also critical for tumor initiation, growth, and metastasis, Cas and NEDD9 are well positioned to contribute to these oncogenic processes. Indeed, mouse models of cancer show that these proteins function during multiple stages of disease progression. Furthermore, in many human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 96 publications
(217 reference statements)
6
40
0
Order By: Relevance
“…5B), further showing that reduced NEDD9 protein level by apigenin was through its post-translation modification. It has been reported that Akt together with other two scaffold proteins p130Cas and NEDD9 forms complex with FAK, Src, and Crk-L proteins (Guerrero et al, 2012). To investigate whether apigenin is able to inactivate FAK, Src, Crk-L, and Akt, phosphorylations of those proteins were examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B), further showing that reduced NEDD9 protein level by apigenin was through its post-translation modification. It has been reported that Akt together with other two scaffold proteins p130Cas and NEDD9 forms complex with FAK, Src, and Crk-L proteins (Guerrero et al, 2012). To investigate whether apigenin is able to inactivate FAK, Src, Crk-L, and Akt, phosphorylations of those proteins were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Cas family proteins have no enzymatic activity but instead function as a platform for the assembly of multiprotein complexes, most notably Src and FAK, to influence cell behavior (Guerrero et al, 2012). Among Cas family members, NEDD9 and p130Cas are extensively studied and implicated in cell motility such as adhesion, cell migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABL-mediated tyrosine phosphorylation of NEDD9 and binding of C3G leads to activation of Rap1 and migration/chemotaxis of lymphoid cells [41]. The NEDD9/CRKL complex promotes actin polymerization and migration and chemotaxis through activation of WASP/ARP2/3 signaling (reviewed in [4, 54]).…”
Section: Altered Nedd9 Expression In Cancermentioning
confidence: 99%
“…NEDD9 plays important roles in cell migration and cell adhesion (reviewed in Bouton et al, 2001, Guerrero et al, 2012, can stabilize focal adhesions and induce cell spreading (Bradshaw et al, 2011, Baquiran et al, 2013, and has emerged as pro-metastasis factor in melanoma (Kim et al, 2006, Ahn et al, 2012, breast cancer (Izumchenko et al, 2009, Little et al, 2014, lung cancer (Miao et al, 2013, Kondo et al, 2012 and glioblastoma (Natarajan et al, 2006). This is the first study to establish a link between NRAGE and NEDD9 but it is interesting to note that other works have implicated NRAGE (Kumar et al, 2011) and NEDD9 (Kong et al, 2011, Ahn et al, 2012 in the negative regulation of E-cadherin-b-catenin and in EMT.…”
Section: Then Releases the P75ntrmentioning
confidence: 99%